Meta-Analysis: Factors Related with Obesity in Adolescents - Karismatika Surya Gumilar; Betriza; Nurcahyo Aji Legowo; Bhisma Murti; Ayu Novita Wulandari (Masters Program in Public Health, 2024)
Background: Obesity is excess body weight above the normal BMI limit. This can be experienced by anyone, starting from children, productive teenagers who do not maintain a healthy lifestyle, which can cause premature death. There are various factors that cause obesity from several research findings. This study aims to analyze and estimate factors that influence the risk of obesity in adole-scents.Subjects and Method: This research is a systematic review and meta-analysis with PRISMA and PICO diagrams. Population= teenagers. Intervention= strong physical activity, high income, female gender, strong consumption of fruit, and high maternal education. Comparison= weak physical activity, low income, male gender, weak consumption of fruit, and low maternal education. Result= obesity. The search for this article came from databases namely PudMed and Science Direct. The article keywords used are